THE SIGNIFICANCE OF SOCIO-ECONOMIC PROBLEMS REFLECTED IN MUKIMI’S CREATION: Umida Azimova , Akbar Raupov - Tashkent state university of economics Uzbek language; literature department‘s big teacher , Umida Azimova; Tashkent state university of economics‘ student, Akbar Raupov (Лучшие интеллектуальные исследования, 2024)
In this article, the author studied the relevance of the problems expressed in Muqimi's works. In the world of literature, there are a number of figures who made a great contribution to the emergence and development of literature, national press and theater art, and it would be unfair to ignore their names and literary and educational activities. The creative heritage of one such figure and creator, Muhammad Aminkhoja Mirzakhoja, was not fully explored even during the period of independence. Mukimi's sharply satirical works ("Mud", "Aroba", "Veksel") have been interpreted in different ways. The unique aspects of the work and poetry of the great poet democrat Mukimi are highlighted.